The role of digital technology in sustaining SMEs in Johannesburg - Arunajalam, Prema (University of the Witwatersrand, Johannesburg, 2023)
This research study aimed to investigate the role of digital technology in sustaining small and medium enterprises (SMEs) in Johannesburg, South Africa. SMEs face resource constraints in establishing digital operations in their organisational framework. The reasons behind the constraints are discussed in this report. A sample group of SME owners was interviewed to gain further insights into the successes and challenges these organizations face. The interviews were conducted across diverse industries to gain multiple perspectives. The key findings noted that many similarities between the organisations and the challenges they face are quite common. Financial constraints are a key finding, with many financing giants not willing to fund an SME due to the nature of the business. These financial constraints, in turn, have several knock-on impacts for the SMEs as they must focus on revenue generation and less focus on optimisation and growth. The findings demonstrate the impact on the sustainability of the SME due to this key factor, in addition to talent management, competition, economic climate and strict legislation. The key outcome of the findings documents a sustainability crisis for the SMEs in Johannesburg. These organisations operate in survival mode with moderate exposure to digital technology due to constraints out of their control. Accessibility to digital technology could create limitless potential for SME growth and profitability, increasing sustainability tenfold and driving a positive upswing in the country's economy.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Digital technology; Small and medium enterprises; SME partnerships; SME platform; SME sustainability; UCTD; SDG-9: Industry, innovation and infrastructure